Distinguish between two Species of streptococcus by sk gene (Medico Legal Update, 2021)
This study aims at the possibility of using the sk gene encoding the Streptokinase protein to differentiatebetween the different species belonging to the genus Streptococcus which can produce this protein., 12bacterial isolates belonging to the genus Streptococcus were obtained, and by using thecaseinolytic assaytest, all the studied isolates gave a positive result with different clear zone diameters around the wells. DNAwas then extracted from the isolated bacteria and used as a template for the amplification of the sk gene usingspecific primers for the gene. The 1300 bp was amplified as PCR product comparing them with the DNAladder. The target gene was obtained from of S. pyogenes and S. dysgalactiae subsp. equisimilis. . The resultwas confirmed by identifying the gene sequences and comparing it with the database in NCBI, which showeda similarity of more than 98% and the percentage of similarity between the genes of the different specieswas more than 99%. The sk gene for both species were digested with BtgZI and MboII restriction enzymes.The results of the agarose gel electrophoresis showed that the gene belonging to the S. pyogenes possessesrestriction sites for BtgZI restriction enzymes that differ in location from that of the S. dysgalactiae subsp.equisimilis. Where the bundles appeared in different locations, which means that the location and numberof restriction sites differ between the two types, and this feature can be used to differentiate between them.